2012
DOI: 10.5194/nhess-12-2271-2012
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing flood resilience through improved risk communications

Abstract: Abstract. A framework of guiding recommendations for effective pre-flood and flood warning communications derived from the URFlood project (2nd ERA-Net CRUE Research Funding Initiative) from extensive quantitative and qualitative research in Finland, Ireland, Italy and Scotland is presented. Eleven case studies in fluvial, pluvial, coastal, residual and "new" flood risk locations were undertaken. The recommendations were developed from questionnaire surveys by exploring statistical correlations of actions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 26 publications
1
69
0
3
Order By: Relevance
“…However, the existing research suggests that current communications are having limited impact on driving risk awareness or resilient behaviours. O'Sullivan et al (2012) examined the impact of flood risk communications across Europe and identified low levels of information penetration and personal preparedness, often accompanied by a high level of These online maps indicate areas of potential flood hazard and differentiate high-, medium-and low-risk categories. Intended to raise awareness of the risk of flooding of those living in at-risk areas Common to the majority of countries in the EU (EXCIMAP 2007a, b;de Moel et al 2009) …”
Section: Current Approaches To Communications In Flood Risk Managementmentioning
confidence: 99%
“…However, the existing research suggests that current communications are having limited impact on driving risk awareness or resilient behaviours. O'Sullivan et al (2012) examined the impact of flood risk communications across Europe and identified low levels of information penetration and personal preparedness, often accompanied by a high level of These online maps indicate areas of potential flood hazard and differentiate high-, medium-and low-risk categories. Intended to raise awareness of the risk of flooding of those living in at-risk areas Common to the majority of countries in the EU (EXCIMAP 2007a, b;de Moel et al 2009) …”
Section: Current Approaches To Communications In Flood Risk Managementmentioning
confidence: 99%
“…responsibility and trust. Apart from experience and emotions, the perceived responsibility of authorities was also found to influence individual risk preparedness in several studies (Botzen et al, 2009a;O'Sullivan et al, 2012;Eiser et al, 2012) although Terpstra et al (2006) found no such correlation. Their results indicate that the influence of perceived responsibility on preparedness is a matter of citizens' trust in their government, and the degree to which citizens trust governments varies according to political and cultural circumstances.…”
Section: Relevant Findings and Open Research Questions On Risk Preparmentioning
confidence: 99%
“…This need of confirmation has been identified by several authors (Mileti and Sorensen, 1990;Sorensen, 2000;O'Sullivan et al, 2012). Parker et al (2009) made a comparison of several studies on the behaviour model across Europe.…”
Section: Methodsmentioning
confidence: 88%